ANALISIS PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL PADA PEMERINTAH KABUPATEN/KOTA DI SUMATERA UTARA - Yonson Pane; Asianna Martini Simarmata; Sri Rezeki; Muhammad Rinaldi; Fitri Yani Panggabean (Universitas Pendidikan Nasional, 2021)
Local government capital expenditures have a significant impact on the economic development of a region. So that aspects of regional original income and balancing funds become an urgent part in the structure of regional revenue and expenditure budgets. The purpose of this paper is to analyze local revenue (PAD) and balancing funds consisting of profit-sharing funds (DBH), general allocation funds (DAU), and special allocation funds (DAK) for capital expenditures. The study was conducted in regencies/cities in North Sumatra using secondary data in the form of data on the Regional Revenue and Expenditure Budget (APBD) realization from 2015 to 2019. The research method uses a quantitative approach. The data analysis technique used multiple regression, which was used to test the five hypotheses, namely to analyze: 1) the effect of PAD and balancing funds consisting of DBH, DAUK, and DAK on capital expenditures simultaneously; 2) the effect of PAD on spending capital; 3) the effect of DBH on capital expenditures; 4) the effect of DAU on capital expenditures; and 5) the effect of DAK on capital expenditures. Thus, the study results prove the hypothesis testing that PAD and balancing funds affect capital expenditure simultaneously. However, partial testing shows that DAU does not affect capital expenditure. At the same time, other independent variables such as PAD, DBH, and DAK affect capital expenditure. The gap in the realization of DAU between local governments is a serious concern for the central government in providing balancing funds. Keywords: capital expenditure, DAK, DAU, DBH, PAD.